The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/spy2.46
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study and analysis of some pseudorandom number generator algorithms

Abstract: In this article, we have investigated the statistical nature of popular pseudorandom number generators (PRNGs) present in the literature and have analyzed their performance against the battery of tests prescribed in NIST SP800‐22rev1a. Different tests performed in this article provide an insight into the PRNGs and have revealed if they are statistically random or not, which is the first criteria in being cryptographically secure. In our study, we have considered the following PRNGs: (a) Linear Congruential Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In such use cases, the stream ciphers [16] will also not prove efficient due to the length of the payload. Moreover, a pseudorandom number generator (PRNG) [17] will be required to ensure their correct operation. The PRNG provides necessary random values on an ongoing basis.…”
Section: Related Workmentioning
confidence: 99%
“…In such use cases, the stream ciphers [16] will also not prove efficient due to the length of the payload. Moreover, a pseudorandom number generator (PRNG) [17] will be required to ensure their correct operation. The PRNG provides necessary random values on an ongoing basis.…”
Section: Related Workmentioning
confidence: 99%
“…It is impossible to consider true randomness in PRNG-generated [5] sequences as they are implemented by software, based on mathematical algorithms and determined by an initial (seed) value. In contrast, the TRNG and QRNG, based on unpredictable physical means, generate the true randomness in the sequence of random numbers.…”
Section: Category Iii: Research Objectives Of Quantum Rngs For Crypto...mentioning
confidence: 99%
“…Pseudorandom number generators (PRNGs) [3,4] are based on algorithms for generating seemingly random numbers, which are determined by their seed, or initial value to enhance security. Shobhit Sinha et al [5] compared various PRNGs based on their statistical randomness and cryptographic security, concluding that some PRNGs performed RNGs' randomness critically depends on the type of RNG.…”
Section: Introductionmentioning
confidence: 99%
“…In [27], different LCG PRNGS algorithms presented different results in the NIST test. Results showed that compared with PRNGs, all LCGs exhibited a poor performance.…”
Section: Related Workmentioning
confidence: 99%